The significance of Sámi rights: law, justice, and sustainability for the indigenous Sámi in the Nordic countries - Cambou, Dorothée; Ravna, Øyvind (Routledge research in polar regions series, 2024)
The significance of Sámi rights in the Nordic countries : an introduction / Dorothée Cambou & Øvind Ravna -- The relevance of the UN Declaration on the Rights of Indigenous Peoples to vibrant, viable, and sustainable Sámi communities / Mattias Åhren -- The survey of property rights in Sámi areas of Norway-with focus on the survey of the Karasjok case / Øyvind Ravna -- Indigenous peoples' right to fish : recent recognition of Sámi rights in Finland through civil disobedience and criminal trial / Martin Scheinin & Pia Nuorgam -- The significance of the Fosen decision and its contribution for protecting the cultural rights of the Sámi in the green transition / Dorothée Cambou -- The interplay of politics and jurisprudence in the Girjas court case / Eivind Torp -- The prohibition to weaken the Sámi culture in international law and Finnish environmental legislation / Leena Heinämäki -- The implementation of Sámi land rights in the Swedish Forestry Act / Malin Brännström -- Sámi rights and conservation issues / Elsa Reimersona & Linn Flodén -- A human rights-based approach to Sámi statistics in Norway / Peter Dawson -- Rendering the invisible visible : Sámi rights and data governance / Tamara Krawchenko & Chris McDonald -- Sámi rights and sustainability in early childhood education and care : sustainability in everyday practices in Norwegian kindergartens / Ingvild Åmot & Monica Bjerklund -- Sámi rights in the sustainable transition : concluding remarks / Christina Allard.